Qualitative identification of imidacloprid in postmortem animal tissue by gas chromatography-tandem mass spectrometry. (2nd September 2019) - Buchweitz, John P.; Viner, Tabitha C.; Lehner, Andreas F.
Abstract: During an avian mass mortality event investigation at the National Fish and Wildlife Forensic Laboratory in Ashland, OR, imidacloprid became an insecticide of concern. A qualitative analytical toxicology screen of seeds, plucks (tongue, esophagus, and trachea), and ventricular contents was requested. A method for the extraction and qualitative analysis of the insecticide in animal tissues was therefore developed. The procedure relies on a combined Food Emergency Response Network (FERN) and QuEChERS ( Qu ick, E asy, Ch eap, E ffective, R ugged, and S afe) approach to sample extraction followed by qualitative analysis by gas chromatography-tandem mass spectrometry. Since imidacloprid is not amenable to the conditions of gas chromatography, a trimethylsilyl derivative was created and characterized. Proposed mechanisms for the creation of this derivative and its mass spectrum are described. The imidacloprid-trimethylsilyl (TMS) derivative was detected in all samples submitted.